KEPATUHAN PEJABAT TATA USAHA NEGARA TERHADAP PUTUSAN PENGADILAN TATA USAHA NEGARA BERDASARKAN ASAS-ASAS PEMERINTAHAN YANG BAIK - Basuki Kurniawan; Sholikul Hadi (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
The main problems to be studied are: (1) how the legal obedience of administrative officials carry out the verdict of administrative court based on good government principles?; (2) Is the arrangement about the obedience of administrative officials already appropriate with good government principles? The method of study use is the juridical normative method. The Approaching of problems use statute approach, conseptual approach, and case approach. Research data source is taken from primary and secondary legal materials. The collected data is qualitatively analyzed by a normative juridical approach. The result of this research are : first, the legal obedience of administration officials is to be consistent do the verdict of administrative court in the framework of implementation good good government principles. The obedience based on legal awareness. Legal awareness and legal obedience very needed for law enforcement in Indonesia. Awareness and legal obedience very needed by every person, in the same manner as the purpose of law. The administrative officials as people which have positions needed to be stressed for being obedience the verdict of administrative court based on good government principles and alse as example to other people. Second, based on article 116 Law Number 5 Year 1986 about Administration Court cpuld be understood that the arrangement obedience the administrative officials not appropriate with good government principles. Based on the research result is recommended, that first, the Administration court based on Law Number 5 Year in the essence is good enough. The obedience of administrative officials still less make the verdict of administration court no run well, so needed to make birocration reformation especially to the interpretation of the legal awareness or increasing awareness from government to all administrative officials as formed the respect existence to the body of government; second, Inobedience the administrative court to the verdict of administration court could be categorize criminal. Third, for the verdict of administration court be able to be done well by administrative officials, so needed control body, although internal and external, hereby the duty of Obudsman National Commision very importence to give attention to the administrative official to do the verdict of administration court.